Hybrid Consensus Models for Public-Private Blockchain Integration (Blockchain, Web3 & Digital Trust Journal p-ISSN 3117-597X and e-ISSN 3117-5988, 2025)
Public blockchains offer trustless settlement and censorship resistance. Private blockchains offer throughput, privacy, and governance control. Enterprises increasingly need both -- and the consensus mechanism at the boundary between the two determines whether the integration actually works or just creates a new category of bridge vulnerability. We present the Hybrid Consensus Integration Framework (HCIF), a systematic design and evaluation of four hybrid consensus models that govern the boundary between public and private chains: anchored finality (private chain commits anchored to public chain proofs), dual-validation (transactions validated on both chains with conflict resolution), tiered consensus (different consensus tiers for different transaction sensitivity levels), and rollup-mediated integration (private execution with public rollup settlement). We test all four on a Fabric-Ethereum integration testbed and a Corda-Cosmos integration testbed, measuring throughput, cross-chain finality latency, privacy preservation, trust model coherence, and GDPR compliance. Our Hybrid Consensus Quality Score (HCQS) shows that rollup-mediated integration achieves the highest overall quality (0.912) while anchored finality offers the simplest deployment path. We also find that dual-validation -- the model most enterprise pilots actually use -- scores lowest (0.768) because it inherits the weaknesses of both chains without the strengths of either.